2015
DOI: 10.1371/journal.pone.0141995
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Electroencephalographic Signal Complexity

Abstract: The study of active and healthy aging is a primary focus for social and neuroscientific communities. Here, we move a step forward in assessing electrophysiological neuronal activity changes in the brain with healthy aging. To this end, electroencephalographic (EEG) resting state activity was acquired in 40 healthy subjects (age 16–85). We evaluated Fractal Dimension (FD) according to the Higuchi algorithm, a measure which quantifies the presence of statistical similarity at different scales in temporal fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 74 publications
10
55
0
Order By: Relevance
“…Males have more GM that is made up of active neurons while females have more WM that is responsible for communication in the brain. Therefore, if MEG is associated more with WM activity, this could explain the differences in the observed regression models [24,25]. Moreover, as noted in [59] the neurons in female brains are more tightly packed in the layers of the cortex when compared to male brains, therefore the more complex evolutions of nmPE observed in the central region could be a reflection of these physiological differences.…”
Section: Age Effectsmentioning
confidence: 85%
“…Males have more GM that is made up of active neurons while females have more WM that is responsible for communication in the brain. Therefore, if MEG is associated more with WM activity, this could explain the differences in the observed regression models [24,25]. Moreover, as noted in [59] the neurons in female brains are more tightly packed in the layers of the cortex when compared to male brains, therefore the more complex evolutions of nmPE observed in the central region could be a reflection of these physiological differences.…”
Section: Age Effectsmentioning
confidence: 85%
“…The signal complexity of EEG, a reflection of the irregularity of the wave shape and dynamics, is reported to be influenced by healthy aging and associated with brain disorders such as AD [73, 74]. Studies using fractal dimension demonstrated that resting-state EEG signal complexity increases from youth to maturity, followed by a reduction in healthy elderly.…”
Section: Eeg Signal Complexity and Agingmentioning
confidence: 99%
“…Studies using fractal dimension demonstrated that resting-state EEG signal complexity increases from youth to maturity, followed by a reduction in healthy elderly. These studies also provided evidence indicating that, in AD, the signal complexity is further reduced as cognitive function declines [73, 74]. …”
Section: Eeg Signal Complexity and Agingmentioning
confidence: 99%
“…Several studies have addressed the variability in the spectral amplitudes of different frequency bands using variance (Hawkes and Prescott, 1973;Oken and Chiappa, 1988), coefficient of variation (Burgess and Gruzelier, 1993;Maltez et al, 2004), and complexity (Fernández et al, 2012;Sleimen-Malkoun et al, 2015). For instance, reductions of the complexity in rsEEG signal have been found not only in healthy aging (Yang et al, 2013;Zappasodi et al, 2015) but also in age-related pathologies such as mild cognitive impairment (McBride et al, 2014) and…”
Section: Introductionmentioning
confidence: 99%